2003
DOI: 10.1590/s1516-89132003000200002
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a peroxidase gene from cassava with potential as a molecular marker for resistance to bacterial blight

Abstract: Cassava bacterial blight (CBB), caused by Xanthomonas axonopodis pv. manihotis, is considered one of the most important bacterial diseases of cassava (Manihot esculenta Crantz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…This finding agrees with what is known about cowpea's defense response mechanism to Xav, represented by a brown-red discoloration without complete collapse of the tissue (Gitaitis 1983). Plants employ a variety of defense mechanisms in response to pathogens, including the use of mechanical barriers, defense proteins and defensive enzymes (Pereira et al 2003). A role for proteins in cell wall structure in bacterial blight disease resistance has been reported by different researchers in several plant species.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding agrees with what is known about cowpea's defense response mechanism to Xav, represented by a brown-red discoloration without complete collapse of the tissue (Gitaitis 1983). Plants employ a variety of defense mechanisms in response to pathogens, including the use of mechanical barriers, defense proteins and defensive enzymes (Pereira et al 2003). A role for proteins in cell wall structure in bacterial blight disease resistance has been reported by different researchers in several plant species.…”
Section: Discussionsupporting
confidence: 89%
“…Flood et al (1995) also suggested that peroxidases might play an important role in resistance to bacterial blight of cassava. A cationic peroxidase gene, MEPX1, was isolated from cassava and the DNA sequence of MEPX1 showed high homology with other plant peroxidase genes and contained a large intron typical of peroxidase genes (Pereira et al 2003). The amino acid sequence had 75% homology with two Arabidopsis thaliana peroxidases.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these genes show similarity to genes involved in defense mechanisms, homologs to R proteins, chitinase and receptor like protein kinases. Data generated through our studies on transcript profiling and by others (Pereira et al, 2001(Pereira et al, , 2003 will permit unraveling the complex pathway signal in the cassava-Xam interaction.…”
Section: Gene Expression Analysis By Transcript Profiling and Ests Anmentioning
confidence: 84%
“…In particular, a-and b-esterases and a peroxidase have been shown to be useful markers of pathogenesis with Xam (Pereira et al, 2001(Pereira et al, , 2003. In our laboratory, high throughput methods of transcript profiling have been developed to study cassava-Xam interactions and to annotate and determine gene functions.…”
Section: Gene Expression Analysis By Transcript Profiling and Ests Anmentioning
confidence: 99%
“…Although the cassava– Xam interaction has been described as pathotype–cultivar specific (Restrepo et al ., 2000a, 2004), cassava bacterial blight resistance mapped to several QTLs located on different linkage groups, highlighting a complex interaction between this plant and the pathogen (Fregene et al ., 1997; Jorge et al ., 2000). Recently, differential expression of esterases and peroxidase have been shown in cassava infected with Xam (Pereira et al ., 2001, 2003). Still, little is known about the molecular mechanisms that lead to resistance to cassava bacterial blight, and therefore we looked for a broad, unbiased tool that would allow the detection of multiple genes putatively associated with resistance.…”
Section: Discussionmentioning
confidence: 99%